Cordia macleodii Hook f. Thomson-A potential Medicinal Plant - Jagriti Chandrakar; A K Dixit (International Journal of Phytomedicine, 2017)
Cordia macleodii Hook. f. & Thoms. belongs to family Boraginaceae, is an endangered medicinal plant, commonly known as “Dahiman” or “Dahipalas”. It is distributed in moist and dry deciduous forests of India such as Chhattisgarh, Madhya Pradesh, Odisha, Chotanagpur and is widely used to cure various diseases. These bioactive compounds made this plant as a valuable potent herbal drug. It contains various bioactive compounds including Phenols, Terpenoids, Saponins, Volatile oils, Flavonoids, Glycosides etc. This review presents the pharmacological property, phytochemical constituents, traditional uses and biological activities of the plant and it will be helpful to explore the knowledge about Cordia macleodii.